Studi Batuan Pada Tanah Beruap Menggunakan SEM-EDX Dan FTIR Di Desa Tempang Minahasa Sulawesi Utara - Drili Lidya Cintana Meruntu; Donny R. Wenas; Sixtus I. Umboh; Cyrke A. N. Bujung (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2023)
North Sulawesi has a fairly large geothermal potential, this is evidenced by the emergence of several types of geothermal manifestations, one of which is in the village of Tempang. The purpose of this study was to determine the microstructure of rocks and the types of rocks contained in the rocks in the manifestation area in the village of Tempang. The method that will be used in this research is to analyze in the laboratory using SEM-EDX and FTIR. The results showed that the mineral content and types of minerals around the geothermal manifestation in the form of steaming ground had 3 mineral elements, namely oxygen, silica, and aluminum. The percentage results from EDX for sample 1 contained Oxygen (O) 43.72%, Silica (Si) 54.12%, and Aluminum (Al) 2.16%. For sample 2, the content of oxygen (O) is 51.10% and silica (Si) is 48.90%. This is in accordance with FTIR measurements obtained that the mineral type of steaming ground rocks in Tempang Village is Quartz (SiO2).